PENINGKATAN KAPASITAS IBU RUMAH TANGGA (NELAYAN) MELALUI PELATIHAN MENJURAI JARING GILLNET DI KAMPUNG NELAYAN KUALA TUNGKAL - Indah, Indah; Hariski, M; Ar Rizky, Andi Wildan; Kurnia, Nina; Triani, Sindi; Putra, Sarma Andika (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, 2023)
The city of Kuala Tungkal is the city where the administrative center of West Tanjung Jabung Regency is located. This city area is within the scope of the Tungkal Ilir District. The city is also the seat of the district administration. This city is located in Jambi Province. One of the locations for counseling from our team is in the Kampung Nelayan Village of Kuala Tungkal with the aim of increasing the capacity of fishing housewives in training to dangle GillNet nets. The benefit of this service is to increase the capacity of housewives and fishermen with the aim of being able to help husbands in hanging nets or repairing broken Gillnet nets. Gill net is a net that is 4 (four) rectangular in shape, has the same size mesh throughout the body of the net, the width is shorter compared to the length. The term GillNet is based on the premise that fish are caught entangled around the operculum of the eye of the net. GillNet nets are prone to tearing and breaking because the ropes of GillNet fishing gear have a small volume. For example, the net rope used is 0.40 mm in size for fishing nets and 0.3 mm for shrimp nets. The net used is monoethylene.